1994
DOI: 10.1002/mc.2940090307
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the methylation status and expression of the raf oncogene in phenobarbital‐induced and spontaneous B6C3F1 mouse liver tumors

Abstract: The liver tumor-prone B6C3F1 mouse (C57Bl/6 female x C3H/He male), in conjunction with the more susceptible C3H/He paternal strain and the resistant C57BL/6 maternal strain, is an excellent model for studying the mechanisms involved in carcinogenesis. The study reported here indicated that the B6C3F1 mouse inherited a maternal raf allele containing a methylated site not present in the paternal allele. Seven days after partial hepatectomy or after administration of a promoting dose of phenobarbital (PB) for 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 39 publications
6
31
1
Order By: Relevance
“…Alterations in DNA methylation patterns can be fixed during DNA replication and evidence suggests that methylation status of a gene can participate, with other gene control mechanisms, to balance the transcriptional level of the gene (25). Hypomethylation is associated with activation of various oncogenes during cancer development, such as c-myc, c-fos, and H-ras in human and rat liver tumors (5,6) and raf (32) in mouse liver tumors. Additionally, c-myc overexpression is correlated with its specific hypomethylation in HL-60 cells (33) and in early rat liver tumors (34).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in DNA methylation patterns can be fixed during DNA replication and evidence suggests that methylation status of a gene can participate, with other gene control mechanisms, to balance the transcriptional level of the gene (25). Hypomethylation is associated with activation of various oncogenes during cancer development, such as c-myc, c-fos, and H-ras in human and rat liver tumors (5,6) and raf (32) in mouse liver tumors. Additionally, c-myc overexpression is correlated with its specific hypomethylation in HL-60 cells (33) and in early rat liver tumors (34).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, changes in genomic methylation, either focal or global, are one of the most consistent findings in human cancers (Gama-Sosa et al, 1983; Makos et al, 1993;Vertino et al, 1993) and an epigenetic mechanism was proposed whereby such changes may contribute to neoplastic transformation by changing the expression patterns of genes involved in growth control (Antequera et al, 1990;Jones et al, 1990). For example, hypomethylation of several proto-oncogenes including c-myc (Munzel et al, 1991;Sharrard et al, 1992), ras (Bhave et al, 1988), raf (Ray et al, 1994), bcl-2 (Hanada et al, 1993), erb-Al (Lipsanen et al, 1988), and c-fins (Felgner et al, 1991) was reported in various types of cancerous tissues. In addition, expression of several tumour-suppressor genes including p16/CDKN2 (Merlo et al, 1995;Gonzalez-Zulueta et al, 1995;Herman et al, 1994), retinoblastoma (Greger et al, 1989;Sakai et al, 1991) and von Hippel Lindau gene (Herman et al, 1994) can be turned off by methylation.…”
mentioning
confidence: 98%
“…The idea that altered DNA methylation plays a variety of roles in carcinogenesis, none of which are mutually exclusive, and involves genetic and epigenetic events (20,32) Tumorigenesis in mouse liver is used as our model system (36,37,(39)(40)(41) and phenobarbital serves as a nongenotoxic rodent tumor promoter (42). We use the B6C3F1 (C57BL/6 x C3H/He) mouse, which is highly sensitive to the development of spontaneous and chemical-induced liver tumors (43,44).…”
Section: The Carcinogen Bioassaymentioning
confidence: 99%
“…The results of our research indicate that the B6C3F1 mouse is deficient with regard to is ability to maintain normal DNA methylation. This appears to underlie in part its uniquely high susceptibility toward development of liver tumors (22,23,36,39,40). We believe that hypomethylation is relevant to tumorigenesis in both rodents and humans (23) and that humans may be less susceptible than rodents in part because of a better ability of human cells to maintain normal patterns of DNA methylation [reviewed in Counts and Goodman (23) and Counts et al (39)].…”
Section: The Carcinogen Bioassaymentioning
confidence: 99%